1995
DOI: 10.1002/cm.970320302
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of amino acids from the carboxy‐terminal end of actin

Abstract: A series of deletions was made from the C-terminal end of actin by inserting termination codons into a full length cDNA of human alpha-skeletal muscle actin. These included deletions of 2, 3, 10, 20, 30, and 40 amino acids. The cDNA clones were transcribed and the resulting mRNAs were translated in vitro using 35S-labeled methionine. The 35S-labeled actin and actin mutants were then tested for the ability to coassemble with carrier actin, bind DNAse I, bind myosin S-1, bind a 27 kDa proteolytic fragment of alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In each study, C-terminal truncations have also been shown to increase the critical concentration, polymerization rate, and rate of ATP hydrolysis of the filaments (47-49). C-terminal truncations have also been shown to lead to conformational changes in the D-loop of SD2, disrupting the interactions between neighboring monomers in the filament, affecting filament stability, and causing observed structural changes to the actin filament (49)(50)(51)(52)(53). Finally, in vivo, truncation of the last 2 residues, C374 and F375, of yeast actin (the last 3 are lethal) leads to a complete loss of actin filamentous structures (54) with a similar effect seen in mammalian cells containing actin having the same mutated C374, which led to a disruption and disorganization of observable filamentous structures with an accompanied increase in diffuse actin staining (55).…”
Section: Discussionmentioning
confidence: 99%
“…In each study, C-terminal truncations have also been shown to increase the critical concentration, polymerization rate, and rate of ATP hydrolysis of the filaments (47-49). C-terminal truncations have also been shown to lead to conformational changes in the D-loop of SD2, disrupting the interactions between neighboring monomers in the filament, affecting filament stability, and causing observed structural changes to the actin filament (49)(50)(51)(52)(53). Finally, in vivo, truncation of the last 2 residues, C374 and F375, of yeast actin (the last 3 are lethal) leads to a complete loss of actin filamentous structures (54) with a similar effect seen in mammalian cells containing actin having the same mutated C374, which led to a disruption and disorganization of observable filamentous structures with an accompanied increase in diffuse actin staining (55).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the N-terminal parts of these two CCTtarget proteins are necessary for correct folding (or for stability) despite their being dispensable for binding to CCT. Xia and Peng (42) reported that region 356-365 plays a key role in maintaining the structural integrity of actin. This is in agreement with our observation that removal of the 25 C-terminal residues results in an increased CCT binding (compared to full-length actin) due to the incapability of this fragment of reaching a correctly folded state.…”
Section: Discussionmentioning
confidence: 99%
“…19,39 Therefore, one of the CCT functions may be to assist actin in bringing its C terminus close to its N terminus. On the basis of EM studies, actin transits from an open to a closed state.…”
Section: Correlating Binding Determinant Information In Actin With Crmentioning
confidence: 99%